2008
DOI: 10.1128/jvi.00638-07
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of HLA Proteins Incorporated by Human Immunodeficiency Virus Type 1 and Assessment of Neutralizing Activity of Anti-HLA Antibodies

Abstract: Human anti-human leukocyte antigen (HLA) antibodies were assessed for neutralizing activity against human immunodeficiency virus type 1 (HIV-1) carrying HLA alleles with matching specificity. Multiparous women carrying anti-HLA antibodies were identified. Plasma samples from those women were confirmed as having antibodies that specifically bound to HLA proteins expressed on the peripheral blood mononuclear cells (PBMCs) of their husbands. A primary HIV-1 isolate was cultured in the husband's PBMCs so that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Proof of principle that antibodies can be useful in targeting viral infection has been obtained for other viruses (15, 16). In addition to direct neutralization of virus, other potential mechanisms by which antibodies can exert a salutary effect include steric hindrance to receptor binding, conformational change in the bound protein, complement-dependent cytotoxicity, viral agglutination, and antibody facilitated phagocytosis (1719). …”
Section: Discussionmentioning
confidence: 99%
“…Proof of principle that antibodies can be useful in targeting viral infection has been obtained for other viruses (15, 16). In addition to direct neutralization of virus, other potential mechanisms by which antibodies can exert a salutary effect include steric hindrance to receptor binding, conformational change in the bound protein, complement-dependent cytotoxicity, viral agglutination, and antibody facilitated phagocytosis (1719). …”
Section: Discussionmentioning
confidence: 99%
“…Such an association may induce conformational changes of gp120 favouring the exposure of cryptic functional epitopes [ 12 ]. It has also been recently reported that viral particles carry more HLA molecules than gp120/gp41 trimers [ 21 ]. The association between a gp120/gp41 trimer and multiple HLA-C molecules might reduce gp120 shedding, thus keeping more functional the trimeric gp120/gp41 complexes on the viral envelope and resulting in increased fusion efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…These results may partially explain previous data, which did not observe sufficient protection against SIV by immunizing macaques with transformed macaques B cells. Furthermore, a recent study demonstrated the absence of both complement-dependent and complement-independent neutralization of HLA-specific Abs against HIV carrying HLA alleles with matching specificity [30]. Therefore, our results may explain conflicting results from different studies indicating that the capacity of HLA allo-specific Abs generated by allo-immunization for the protection against HIV might depend on the feature of the generated Abs (e.g.…”
Section: Discussionmentioning
confidence: 61%